Aplikasi Sistem Informasi Geografis Persebaran Lokasi Pos Pemadam Kebakaran Berbasis Android - Purnamansyah, Akhmad; Ibrahim, Moh. Galuh Esa (LPPM UNU CIREBON, 2020)
Cirebon District Fire Service which serves the community and helps the community when a fire accident occurs. Information about the location of the nearest fire station is not widely known by some people. This of course hampers the process of fire disaster management and services for the community. The purpose of this research is to produce a Geographical Information System application for the distribution of fire station locations based on Android that can be easily accessed by the public. Geographical Information System uses Hybrid Mobile technology which is implemented into the Dart and Flutter programming languages. In this study, the data collection techniques used were observation, interviews and literature study, with the testing method using blackbox testing. From the results of the system implementation, it can be concluded that using the Android-based Geographical Information System Application can help and provide convenience for the community in obtaining information and assistance regarding the location of the nearest fire station.